Numerical Investigation of Performance Improvement and Erosion Characteristics of Vortex Pump Using Particle Model - Daoxing Ye; Hao Li; Qiuyan Ma; Qibiao Han; Xiulu Sun (Shock and Vibration)
Vortex pump has characteristics of low efficiency and serious surface erosion of blade, which seriously affects service life. Therefore, it is particularly important to improve the efficiency of vortex pump and reduce erosion of blade surface. In this investigation, the design of experiment was used to determine the test plan and the number of samples tested. The relationship between geometric factors of vortex pump and efficiency and erosion rate of blade was established using the kriging approximation model. The genetic algorithm solved the multiobjective optimization and obtained the Pareto front solution using NSGA-II. The results showed that the width of nonblade cavity of the vortex pump is reduced by 18.93%, the number of blades of the impeller is increased by one, and the outlet width of the blade is increased by 19.81%. The performance after optimization is significantly improved compared with the original prototype. At design flow rate, the efficiency of the vortex pump increases by 3.24%, while the efficiency increases by 2.59% and 6.24% at 0.8Qd and 1.2Qd, respectively. The maximum erosion rate of blade surface 8.52 × 10−4 kg/(m2·s) is reduced to 7.18 × 10−4 kg/(m2·s) at 1.0Qd by optimization, which is reduced by 15.73%. The blade erosion after optimization is significantly controlled, and the angle of particle hitting blade surface is reduced.